2015
DOI: 10.1016/j.ijid.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Current clinical, laboratory, and treatment outcome characteristics of visceral leishmaniasis: results from a seven-year retrospective study in Greece

Abstract: VL is still a common disease in endemic areas, affecting immunocompetent and immunocompromised patients. Its diagnosis is challenging, and molecular techniques are valuable and helpful tools to achieve this. Treatment with L-AMB is safe and very effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 43 publications
1
26
0
2
Order By: Relevance
“…Fever in VL is almost always present , splenomegaly in 23.7% to 100% of patients , elevated liver enzymes in 42–85% of cases , increased levels of LDH and CRP are seen in 72.5% and 83.1% of cases . In the patient presented here, CRP was elevated from the first day of presentation and remained unchanged until initiation of therapy, LDH started rising with the appearance of pancytopenia.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Fever in VL is almost always present , splenomegaly in 23.7% to 100% of patients , elevated liver enzymes in 42–85% of cases , increased levels of LDH and CRP are seen in 72.5% and 83.1% of cases . In the patient presented here, CRP was elevated from the first day of presentation and remained unchanged until initiation of therapy, LDH started rising with the appearance of pancytopenia.…”
Section: Discussionmentioning
confidence: 59%
“…Weeks to months after a trip to endemic regions, fever, loss of appetite, weight loss, lymphadenopathy may occur, often accompanied by pancytopenia, hepatosplenomegaly, and elevated liver enzymes . The infection may mimic leukemia, viral infections, or autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization recommends L‐AmB as the first choice for VL caused by Leishmania infantum due to the shorter duration of drug therapy and lower toxicity compared with conventional amphotericin B and MA . Although studies have indicated the efficacy and safety of L‐AmB therapy, its use is still limited due to its high cost …”
Section: Case Descriptionmentioning
confidence: 99%
“…High doses are needed to achieve a cure, and irreversible diabetes has been reported in 4%-12% of cases. 44 The primary action of pentamidine against Leishmania is not clearly understood, but the drug's structural characteristics and experimental results suggest that the active transport system and the mitochondria are the final sites of inhibition. A series of experiments showed that it acts as an inhibitor of polyamine uptake and the arginine transporter, 45 while other findings indicate the mitochondrial replication system as possible target (through inhibition of topoisomerase II activity).…”
mentioning
confidence: 99%